2023
DOI: 10.1186/s12964-023-01254-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone-binding globulin (SHBG) mitigates ER stress and improves viability and insulin sensitivity in adipose-derived mesenchymal stem cells (ASC) of equine metabolic syndrome (EMS)-affected horses

Nabila Bourebaba,
Mateusz Sikora,
Badr Qasem
et al.

Abstract: Background Equine metabolic syndrome (EMS), which encompasses insulin resistance, low-grade inflammation and predisposition to laminitis is a critical endocrine disorder among the most prevalent conditions affecting horses from different breeds. According to the most recent research, low human sex hormone-binding globulin (SHBG) serum levels correlate with an increased risk of obesity, insulin resistance and diabetes, and may contribute to overall metabolic dysregulations. This study aimed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Furthermore, a study proposed that SHBG might serve as a promising therapeutic option for liver metabolic disorders [18]. Other studies have indicated that SHBG can improve lipid metabolism [19], and enhance insulin sensitivity [20]. While some researches has explored the relationship between metabolic syndrome and SHBG levels [21][22][23][24][25], the association between SHBG and metabolic syndrome remains a topic of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study proposed that SHBG might serve as a promising therapeutic option for liver metabolic disorders [18]. Other studies have indicated that SHBG can improve lipid metabolism [19], and enhance insulin sensitivity [20]. While some researches has explored the relationship between metabolic syndrome and SHBG levels [21][22][23][24][25], the association between SHBG and metabolic syndrome remains a topic of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study proposed that SHBG might serve as a promising therapeutic option for liver metabolic disorders [ 15 ]. Some studies have indicated that SHBG can improve lipid metabolism [ 16 ], and enhance insulin sensitivity [ 17 ]. While some researches has explored the relationship between MetS and SHBG levels [ 18 23 ], the association between SHBG and MetS remains a topic of debate.…”
Section: Introductionmentioning
confidence: 99%